2016
DOI: 10.1111/tid.12503
|View full text |Cite
|
Sign up to set email alerts
|

Whooping cough in a renal transplant recipient

Abstract: Whooping cough is a respiratory infection with a severity that varies with age, immune status, and probably with other factors such as the degree of exposure and the virulence of the organism. The most frequent microorganism responsible for whooping cough is Bordetella pertussis. We present the case of a 62-year-old renal transplant recipient presenting with typical and severe manifestations of whooping cough caused by B. pertussis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To our knowledge, this is the second reported case of B pertussis infection in a renal transplant recipient and the first patient demonstrating co‐infection with B parapertussis/bronchiseptica . We considered the possibility of this case patient having a monomicrobial infection with either B parapertussis/bronchiseptica or B pertussis .…”
Section: Discussionmentioning
confidence: 81%
“…To our knowledge, this is the second reported case of B pertussis infection in a renal transplant recipient and the first patient demonstrating co‐infection with B parapertussis/bronchiseptica . We considered the possibility of this case patient having a monomicrobial infection with either B parapertussis/bronchiseptica or B pertussis .…”
Section: Discussionmentioning
confidence: 81%
“…24 Six case studies reported mild to severe pertussis disease in adults aged 31-82 years with underlying conditions as Diabetes Mellitus Type II, Wegener's granulomatosis, multiple myeloma, renal transplantation, and acquired immune deficiency syndrome. [41][42][43][44][45][46] Mannose-binding lectin deficiency (MBL) One study evaluated the risk of pertussis in patients with MBL. Among study participants of all ages (median age of 15 years, age range: 1-71), severe MBL deficiency was significantly more frequent among the 125 pertussis patients than among the 430 controls (11.2% vs. 5.8%, odds ratio 2.0 [95% CI: 1.0-4.1]).…”
Section: Immunocompromising Conditionsmentioning
confidence: 99%
“…Tetanus, diphtheria, and pertussis are rare bacterial VPIs in adult SOT recipients [3][4][5][6]. In a recent cohort of SOT recipients from Switzerland, no case of diphtheria or tetanus was found within 12 years post-transplantation; however, two cases of pertussis were detected, resulting in an incidence rate of 10 per 100,000 person-years of follow-up [2].…”
Section: Introductionmentioning
confidence: 99%
“…In France, another case involved a renal transplant recipient who developed generalized tetanus 12 years post-transplantation; although anti-tetanus antibodies were detectable, the patient required prolonged intensive care and could not ingest food for 11 days due to trismus [4]. Additional reports from the USA and Spain have described pertussis infections in renal transplant recipients that were diagnosed and treated after significant delays, with patients experiencing a month of coughing [5,6]. Due to the potential risk of severe infection and poor outcomes, vaccination with tetanus and diphtheria toxoids vaccine (Td) or tetanus, diphtheria, and acellular pertussis (Tdap) vaccine are recommended in adult SOT recipients before or after transplantation [7,8].…”
Section: Introductionmentioning
confidence: 99%